2010
DOI: 10.1007/s12289-010-0984-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of yield criteria for forming simulations based on residual stress measurement

Abstract: Process induced anisotropy in sheet metal is accounted for in analytical modeling by anisotropic yield criteria. The suitability of a yield criterion for predicting sheet metal forming process is generally validated by way of its ability to predict surface strains. However, the sensitivity of surface strains to yield criteria is dependent upon strain modes, with plane strain mode exhibiting higher sensitivity. To eliminate dependency on strain modes, stresses are used to evaluate yield criteria, since forming … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…As Figure shows, when only the effect of springback is considered, the residual stress decreases after the detachment of the tools from the partially deformed cup. After removing the tools, the stress field in the cup relaxes and redistribute to lower levels, which is in a good agreement with other reports …”
Section: Fe Simulation Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…As Figure shows, when only the effect of springback is considered, the residual stress decreases after the detachment of the tools from the partially deformed cup. After removing the tools, the stress field in the cup relaxes and redistribute to lower levels, which is in a good agreement with other reports …”
Section: Fe Simulation Resultssupporting
confidence: 92%
“…After removing the tools, the stress field in the cup relaxes and redistribute to lower levels, which is in a good agreement with other reports. [32,33] Figure 6 shows the contours of the von Mises equivalent stress distribution at the same drawing depth (13.5 mm) for the V-mode and three sets of simulated A-D modes. This figure indicates that the stress is mostly concentrated in the punch radius area.…”
Section: Fe Simulation Resultsmentioning
confidence: 99%
“…The accuracy of theoretical prediction is highly dependent on the choice of yield criterion. 27 Appropriate choice of anisotropic yield criterion will enable a more accurate prediction of variation of weld strength with orientation.…”
Section: Resultsmentioning
confidence: 99%
“…Barlat89 criterion is used for the prediction, as Kuwabara et al concluded that the Hosford yield criterion (Barlat89 is a generalization of Hosford criterion) fits the experimental data better than the Hill48 criterion. Hariharan et al 20,34 have recently compared Hill48 and Barlat89 criteria for multiple strain modes and concluded that the results predicted by Barlat89 criterion are closer to experiments than the Hill48 criterion. The experimental data are compared in Figure 7 against subsequent yield loci predictions using both average n and effective n. In the present study, the difference between the predictions using constant average n and effective n is marginal, with minor difference at specific stress ratios like 0.5, 0.75, etc.…”
Section: Application Of Varying Effective Strain Hardening Exponentmentioning
confidence: 98%